Effect of cisplatin in Mytilus galloprovincialis and of cyclophosphamide, tamoxifen and cisplatin on Ca2+ATPase - Morais, Matilde (2015)
In the last decade anti-cancer drugs, such as cisplatin, tamoxifen and cyclophosphamide, have seen their use greatly increase. Cisplatin is one of the most common anti-cancer drugs used in the EU which ubiquitous occurrence in surface waters, like rivers and estuaries, is related to the poor removal capacities of waste-water treatment plants (WWTPs). These drugs are genotoxic, cytotoxic, mutagenic and teratogenic. Therefore, this study includes a multibiomarker response analysis on mussel Mytilus galloprovincialis during two weeks of exposure to 100ng/l of cisplatin assessing antioxidant enzyme activity - catalase (CAT), glutathion-S-transferase (GST); lipid peroxidation (LPO) coupled with an enzyme assay to determine the inhibition effect of cisplatin, tamoxifen and cyclophosphamide (IC50) in the Ca2+ -ATPase. Results show that cisplatin does not seem to have an effect in the activity of CAT, GST and LPO and that its IC50 is 13.7 mM. The effect of the other two anti-cancer drugs were tamoxifen 0.271 mM and cyclophosphamide 1.134 μM. which makes Cisplatin much less dangerous than the other two anti-cancer drugs.